Free Trade in "Corn": A Statistical Study of the Prices and Production of Wheat in Great Britain from 1873 to 1914 - Olson, Mancur; Harris, Curtis C. (Quarterly Journal of Economics, 1959)
I. The problem, 145. — II. The background, 146. — III. The effects on acreage, 148. — IV. The trend, 150. — V. Barley-wheat price ratio, 154. — VI. The models, 155. — VII. Relationship of regression lines and function elasticities, 157. — VIII. Conclusions, 165.